Hereditary hypertriglyceridemic rat: a suitable model of cardiovascular disease and metabolic syndrome? - Zicha, J; Pechánová, O; Cacányiová, S; Cebová, M; Kristek, F; Török, J; Simko, F; Dobesová, Z; Kunes, J (Physiological research, 2006)
Hypertriglyceridemia and hypertension seem to be very important cardiovascular risk factors. The Prague hereditary hypertriglyceridemic (hHTG) rat was developed as a model of human hypertriglyceridemia. It was demonstrated that these rats are not obese, they are hypertensive and insulin resistant and they have some disturbances in glucose metabolism. Several QTLs were identified for blood pressure, its particular components (dependent on major vasoactive systems) and plasma triglycerides throughout the genome of hHTG rats by using of F(2) hybrids strategy. It is evident that hHTG rats are a suitable model for the study of metabolic disturbances in relation to blood pressure as well as for the search of genetic determinants of these abnormalities. Numerous abnormalities of blood pressure regulation as well as alterations in the structure and function of cardiovascular apparatus (heart, conduit and resistance arteries) were found in hHTG rats. A special attention was paid to possible changes in the efficiency of various vasoactive systems such as nitric oxide, renin-angiotensin-aldosterone system and sympathetic nervous system, which seem to contribute substantially to cardiovascular and/or metabolic abnormalities observed in Prague hereditary hypertriglyceridemic rats.
Keywords: metabolický syndrom; Hypertriglyceridemia; Rats; hypertriglyceridemie; Animals; synthasa oxidu dusnatého; krysa rodu Rattus; Humans; lidé; Disease Models, Animal; inzulinová rezistence; hypertenze; Metabolic Syndrome; Nitric Oxide Synthase; Insulin Resistance; Hypertension; zvířata; modely nemocí na zvířatech